2020
DOI: 10.3389/fpls.2020.00895
|View full text |Cite
|
Sign up to set email alerts
|

AP2/DREB Transcription Factor RAP2.4 Activates Cuticular Wax Biosynthesis in Arabidopsis Leaves Under Drought

Abstract: Drought is a critical environmental stress that limits growth and development of plants and reduces crop productivity. The aerial part of land plants is covered with cuticular waxes to minimize water loss. To understand the regulatory mechanisms underlying cuticular wax biosynthesis in Arabidopsis under drought stress conditions, we characterized the role of an AP2/DREB type transcription factor, RAP2.4. RAP2.4 expression was detected in one-week-old seedlings and rosette leaves, stems, stem epidermis, cauline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…Transcription factors contain one or more specific DNA-binding domains and are essential in regulating gene expression throughout the life cycles of higher plants ( Hao et al, 1998 ). The AP2/ERF (APETALA2/ethylene-responsive element binding factors) TFs are a large group that is mainly found in plants ( Yang S. U. et al, 2020 ). The TFs of this family are important regulators of many biological and physiological processes, including plant morphogenesis, responses to various stresses, hormone signal transduction, and biosynthesis of metabolites ( Feng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factors contain one or more specific DNA-binding domains and are essential in regulating gene expression throughout the life cycles of higher plants ( Hao et al, 1998 ). The AP2/ERF (APETALA2/ethylene-responsive element binding factors) TFs are a large group that is mainly found in plants ( Yang S. U. et al, 2020 ). The TFs of this family are important regulators of many biological and physiological processes, including plant morphogenesis, responses to various stresses, hormone signal transduction, and biosynthesis of metabolites ( Feng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…DREBs have been extensively examined under abiotic stress, where they respond to and positively regulated drought, cold, salt, and heat tolerance by regulating stress-responsive genes ( Xie et al, 2019 ). Drought- and salt- inducible Arabidopsis RAP2.4 is reported to regulate multiple developmental processes and drought stress tolerance ( Lin et al, 2008 ; Yang et al, 2020 ). In this study, IbRAP2.4 expression was highly detected in sweetpotato roots ( Figure 2A ), and induced by treatments of salinity, dehydration, ethylene, and IAA ( Figure 2B ).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the upregulated genes due to B. cinera infection, which include CCR2 , CYP71A13 , NATA1 , SRG1 , and EL13-2 , are responsive to phytohormones (salicylic acid, methyl-jasmonate, 1-aminoacyclopropane-1-carboxylate, and abscisic acid), indicating that hormones play a dominant role in the transcriptional programming of the Arabidopsis defence response towards B. cinera infection. Alongside that, the potential of the RAP2.4 gene to serve in plant defence by regulating endogenous signal molecules and pathogen-derived effectors was also highlighted, whereas previous research had reported a similar elevation in gene expression under drought stress [ 75 ]. Thus, the information of the DEGs in response to plant infection makes it possible to understand the mechanisms underlying the plant defence system, which can subsequently be utilised to develop disease-suppressive soils and enable genetic modification of the crop with the desired defensive traits.…”
Section: Disease-suppressive Soils As Greener Alternatives Against Bi...mentioning
confidence: 99%